2010
DOI: 10.1051/0004-6361/201014302
|View full text |Cite
|
Sign up to set email alerts
|

Radioactive26Al from the Scorpius-Centaurus association

Abstract: Context. The Scorpius-Centaurus association is the most-nearby group of massive and young stars. As nuclear-fusion products are ejected by massive stars and supernovae into the surrounding interstellar medium, the search for characteristic γ-rays from radioactivity is one way to probe the history of activity of such nearby massive stars on a My time scale through their nucleosynthesis. 26 Al decays with a radioactivity lifetime τ ∼1 My, 1809 keV γ-rays from its decay can be measured with current γ-ray telesco… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
129
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(145 citation statements)
references
References 53 publications
16
129
0
Order By: Relevance
“…At such galactocentric distances, individual 26 Al-emission regions are only a few, they are faint, and they are not associated with spiral arms. Thus, we do not expect large 26 Al velocity asymmetries, in good agreement with the measurements in Cygnus (Martin et al 2009) and Scorpius-Centaurus (Diehl et al 2010). Bagetakos et al (2011).…”
Section: Model For the 26 Al Kinematicssupporting
confidence: 89%
“…At such galactocentric distances, individual 26 Al-emission regions are only a few, they are faint, and they are not associated with spiral arms. Thus, we do not expect large 26 Al velocity asymmetries, in good agreement with the measurements in Cygnus (Martin et al 2009) and Scorpius-Centaurus (Diehl et al 2010). Bagetakos et al (2011).…”
Section: Model For the 26 Al Kinematicssupporting
confidence: 89%
“…Yet, the irregularity of the large-scale emission as seen by COMPTEL from Galactic 26 Al already suggested that the massive-star population in the Galaxy may be more clumpy than such large-scale models describe. The localized 26 Al emission seen from the Cygnus and Sco-Cen regions [84,28] supports this view. Accounting for such localized enhancements, with more-advanced INTEGRAL measurements the Galactic mass of 26 Al has been re-determined as ranging from 1.5 to 3.6 M , considering all uncertainties.…”
Section: Al In the Galaxymentioning
confidence: 63%
“…11, and in specific, localized regions (see below). In the inner Galactic ridge, a flux at 1808.63 keV of (2.63 ±0.2) 10 −4 ph cm −2 s −1 rad −1 has been derived [28]. The total mass of 26 Al in the Galaxy had been inferred from earlier COMP-TEL measurements to be 2-3 M [101].…”
Section: Al In the Galaxymentioning
confidence: 99%
See 2 more Smart Citations